The Principal and School Improvement Theorising Discourse, Policy, and Practice - Heffernan, Amanda (Educational Leadership Theory,, 2018)
This book investigates the localised effects of reform by exploring the impact of a school improvement policy agenda on the work of three experienced principals. It presents three longitudinal case studies within a shared specific leadership context in Queensland, Australia. The case studies enable an exploration of the way the principalship in this context has evolved over time, providing deep insights into the practices and beliefs of three experienced school leaders working in a period of rapid and urgent systemic reform. The nature of global reform policy borrowing means that the research and the findings within this monograph are relevant for international audiences. The book describes a new way to understand and theorise the effects of reform policies and associated pressures on school leaders. Using post-structural theory, it provides a better understanding of the specific effects of reform policy ensembles, particularly when combined with an analysis of the ways policy and discourse work together at a wider level to create an environment that disciplines the principalship. Further, it sheds lights on the means of complying with or contesting policy influences and how the work of leaders has changed over time.